Evaluation of Investment Returns through Equity Crowdfunding Platforms in Indonesia in 2023 - Eric S Wicaksono; Zuliani Dalimunthe (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This research aims to investigate the factors influencing Return on Investment (ROI) in SMEs in Indonesia utilizing equity crowdfunding as a funding method. This research employs a quantitative approach with the aim of describing the relationship between the variables under examination, namely the relationship between equity crowdfunding and the financial performance of SMEs in Indonesia. The population in this study includes all SMEs in Indonesia that have engaged in equity crowdfunding up to the year 2023. A sample of 31 SMEs was selected for the study. Data analysis techniques involved testing the research model to ensure its acceptance and produce valid and reliable findings. This testing process included several essential steps, namely classic assumption tests, F-tests, and t-tests. The results of the study indicate that the campaign duration in equity crowdfunding has a significant relationship with the Return on Investment (ROI) obtained by SMEs. The variable 'Campaign Duration Score' shows a statistically significant relationship, supporting the hypothesis that the longer the campaign duration, the higher the ROI that can be achieved. This suggests that longer campaigns provide investors with more time to research and make better investment decisions, ultimately increasing trust levels and potential ROI. The amount of funds raised during the equity crowdfunding campaign does not have a significant relationship with the ROI obtained by SMEs. The variable 'Log Raised Funds' does not show statistical significance, challenging the assumption that the amount of funds raised is a key factor in determining ROI. This indicates that other factors such as efficient fund usage, post-funding business strategies, and market conditions may have a greater influence on SMEs' financial success post-crowdfunding. The industry sector in which SMEs operate has a significant impact on ROI. The variable 'Industry Score' shows a significant negative impact on ROI, especially for SMEs in the Restaurant/Food & Beverage sector compared to other sectors. This emphasizes the importance of industry context in determining financial performance after obtaining funding through equity crowdfunding. The Restaurant/Food & Beverage sector may face additional challenges such as intense competition, lower profit margins, and consumer demand fluctuations, which can reduce ROI potential.